The Suggestion of an Economic Growth Model: The Analysis of Production in Ancient Rural Settlement - Necip Ozgur Iyilikci (European Scientific Journal, ESJ, 2017)
In this paper, the way to determinant of growth and development is tried to be introduced with a theoretical model that suggests growth is the result of technological development. Countries’ own technological development and technology creating centre can be generated by connecting this to the model of the production, reproduction and redistribution systems of crops in an old village. This traditional way of producing crops in the past is taken as a clue to create technology centre for countries today. The point is how we can produce technology by local technological firms now based on the acceptance of certain principles as old villagers produced, reproduced and distributed in the past. Today, the state replaced the duties of chief of the village providing trust and local technological firms replaced households units of the village where each of them have certain duties like reciprocity and cooperation towards each other. ‘Clustering’ is an important concept in growth and development and in this paper ‘social clustering’ is suggested and validity and sustainability of this is searched. Free market is necessary but not sufficient condition for growth. In order to attain high growth rates, a mixture of competition and co-operation is required. Free Market gives special importance to competition that may undermine the trust in the society and may therefore lead to a weakening of consensus necessary for sustaining uninterrupted growth over time. The state can play a positive role in the development process by its organizational characteristics including the quality of its personnel, degree of its autonomy. Therefore, technology creating centers under the leadership of state could reinforce cooperation and make selective firms more competitive in international markets.